Dieksis dalam film pendek KAI - Pulang: Analisis pragmatik - Gusvita, Widya; Apriyani, Yolanda (JURNAL PENDIDIKAN DAN SAINS, 2024)
The aim of this research is to identify, define, analyze and classify various types of deixis and the use of deixis in the short film Pulang. This study uses qualitative methodology and descriptive analysis. The focus of the research is the short film Pulang. The stages of this research consist of; 1) the author prepares to find information related to this research, and watches the short film Pulang. 2) The following are the activities used to collect data. To make data identification easier, films are taken from the internet. In every film there is deixis in it, the things obtained are then recorded by marking. 3) Use of descriptive methods in data analysis. And examined based on the types of deixis and their use.